Greek Preschool Teachers' Perceptions about the Effective Strategies for Bullying Prevention in Preschool Age - Markogiannakis, Georgios (2017)
The aim of the present research is to explore preschool teachers' perceptions about the effective strategies for bullying prevention in preschool context. The sample of this research study was 164 preschool teachers from Greece. Data were collected by a questionnaire that was based on previous research. The findings show that teachers regard that classroom activities for diversity acceptance, the development of empathy, the cooperation between school and family, the implementation of socio-emotional learning programs in school context and teacher training, are among the most effective strategies. They also value the cooperation between school, family, and community services for bullying prevention as well as peer support and the creation of prevention activities and material such as videos. Research findings may be utilized for designing teacher training and professional development programs aiming at preventing school bullying at an early age